Studies of syngas cleaning technologies suitable for power generation from biomass oil palm shells - Chin, Lai Fui Bridgid (Curtin University, 2011)
The efficiency of the gas cleaning step is one of the fundamental steps to the successful operation of biomass gasification technologies for power generation. Catalytic cracking is selected as the hot gas cleaning technology for this research using zeolite HZSM-5 catalyst in order to reduce tar produced from palm shells gasification in the laboratory scale fixed bed gasifier. The catalyst load of 2, 5 and 10 weight % of the weight of palms shells has been tested in experiment. Gas chromatographic analysis of the tar produced has been conducted along with the study of biomass gasification index (BGI), emissions of CO, NO, and SO2. It is observed that the tar contains a high concentration of carbolic acid (5 to 8 volume %) in the gas in the range of oxygen to nitrogen flowrate ratio from 0.10 to 0.15 studied. The carbolic acid concentration decreases in the tar with the oxygen to nitrogen ratio increase.The overall heterocyclic aromatics in the tar content are comparable when operating with oxygen to nitrogen ratio of 0.12 and 0.15.The lowest concentration of carbolic acid has been achieved when 5 weight % of HZSM-5 catalyst is used with a reduction of 99% and 79% for oxygen to nitrogen ratio of 0.10 or 0.15 respectively when compared to the carbolic acid concentration without the presence of the catalyst. At the same time higher percentage of the catalyst results in less chemical compounds found in tar. Tar content increased as lower concentration of oxygen content in gas mixture or larger palm shells particle size was used.Lower CO emission produced when lower oxygen content in gas mixture was used. Oxygen to nitrogen ratio has the most significant effects on the NO production compared to palm shells particle size. Both oxygen to nitrogen ratios and palm shells particle size does not have any significant effects on the SO2 production. Higher BGI could be obtained if larger palm shells particle sizes are used in this system. Suitable correlations for the tar removal cleanup for syngas derived from biomass oil palm shells at different operating parameters when using HZSM-5 catalyst have been developed from the interpolation of the experimental data obtained.